Biomimetic surface topography as a potential modulator of macrophages inflammatory response to biomaterials - Monteiro, N. O. (2022)
The implantation of biomaterial devices can negatively impact the local microenvironment through several processes including the injury incurred during the implantation process and the associated host inflammatory response. Immune cell responses to implantable biomaterial devices mediate host-material interactions. Indeed, the immune system plays a central role in several biological processes required for the integration of biomaterials such as wound healing, tissue integration, inflammation, and foreign body reactions. The implant physicochemical properties such as size, shape, surface area, topography, and chemistry have been shown to provide cues to the immune system. Its induced immune-modulatory responses towards inflammatory or wound healing phenotypes can determine the success of the implant. In this work, we aim to evaluate the impact of some biomimetic surface topographies on macrophages' acute inflammatory response. For that, we selected 4 different biological surfaces to replicate through soft lithography on spin casting PCL membranes. Those topographies were: the surface of E. coli, S.eppidermidis and L929 cells cultured in polystyrene tissue culture disks, and an Eggshell membrane. We selected a model based on THP-1-derived macrophages to study the analysis of the expression of both pro-inflammatory and anti-inflammatory markers. Our results revealed that depending on the surface where these cells are seeded, they present different phenotypes. Macrophages present a M1-like phenotype when they are cultured on top of PCL membranes with the surface topography of E. coli and S. epidermidis. When cultured on membranes with L929 monolayers or Eggshell membrane surface topography, the macrophages present a M2-like phenotype. These results can be a significant advance in the development of new implantable biomaterial devices since they can help to modulate the inflammatory responses to implanted biomaterials by controlling their surface topography.